2017
DOI: 10.1007/15695_2017_24
|View full text |Cite
|
Sign up to set email alerts
|

Skin Graft Fixation in Severe Burns: Use of Topical Negative Pressure

Abstract: Over the last 50 years, the evolution of burn care has led to a significant decrease in mortality. The biggest impact on survival has been the change in the approach to burn surgery. Early excision and grafting has become a standard of care for the majority of patients with deep burns; the survival of a given patient suffering from major burns is invariably linked to the take rate and survival of skin grafts. The application of topical negative pressure (TNP) therapy devices has demonstrated improved graft tak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…1,2,[5][6][7][8][9][10] In addition, some reports discuss the use of VAC therapy to fix split-thickness skin grafts on free muscle flaps. [11][12][13][14][15][16][17] In 2018, Chim et al applied VAC on free transplanted muscle flaps of lower extremity to study the effect of VAC therapy on postoperative flap edema. Their results showed that immediate application of VAC on free muscle flaps of lower extremity did not compromise flap survival nor overall outcomes and resulted in decreased flap thickness and a better aesthetic outcome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2,[5][6][7][8][9][10] In addition, some reports discuss the use of VAC therapy to fix split-thickness skin grafts on free muscle flaps. [11][12][13][14][15][16][17] In 2018, Chim et al applied VAC on free transplanted muscle flaps of lower extremity to study the effect of VAC therapy on postoperative flap edema. Their results showed that immediate application of VAC on free muscle flaps of lower extremity did not compromise flap survival nor overall outcomes and resulted in decreased flap thickness and a better aesthetic outcome.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,5–10 In addition, some reports discuss the use of VAC therapy to fix split-thickness skin grafts on free muscle flaps. 11–17…”
Section: Introductionmentioning
confidence: 99%